Graphene quantum dots as drug carriers - Chen, Jie (2015)
In this work, graphene quantum dot (GQD), a nanoscale fluorescent material, was successfully obtained through a ‘top-down’ method, using carbon black as a source. The as-prepared GQDs were applied as a drug carrier to target Doxorubicin (DOX) to tumor cells. It was found that in PBS solution, the loading efficiency of DOX onto the surface of GQDs reached highest at pH 8. Besides, at pH 6, most of the drugs were released from the GQD matrix after 24 hours. The results indicate that the loading and release behavior of DOX can be controlled by adjusting the pH of the solution, which is advantageous since the tumor cells have a slightly acidic environment. The cell viability test also showed that with the presence of GQD, DOX has a more significant killing efficiency.